GAMBARAN TERSANGKA PENDERITA MALARIA DI WILAYAH KERJA PUSKESMAS PANYABUNGAN JAE KECAMATAN PANYABUNGAN KABUPATEN MANDAILING NATAL TAHUN 2015 - Delima Saima Putri; Hiswani .; Sri Novita Lubis (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
Malaria is a disease caused by parasite of the genus Plasmodium that transmission whilebite of Anopheles spp. Annual Parasit Incidence (API) Indonesia in 2015 is 0,99%. API in Sumatera Utara in 2014 is 1 %. API at District of Mandailing Natal in 2014 is 12,4 %, and Panyabungan in 2014 with API 22,2 %. This research has descriptive study with case series design. The purposed to knowing the description of malaria patients suspect of Panyabungan Jae public health center District Mandailing Natal in 2015. Population is all of data malaria patients suspect had laboratory result about 206 people. Sample is some of the population about 136 people, taken with Systematic Random Sampling. Data has analyzed statistic with using Chi- Square test. Sosiodemographic higest proportion in the age group 5-14 years old (27,9%), male (52,2%), school (34,6 %), and living in Panyabungan (93,4%). Result of laboratory of malaria clinis is higest (79,4%).The type of malaria parasite is Plasmodium falciparum (96,4 %). Symptom of malaria is fever (100%). The type of treatment of malaria is ACT (67,9%). There is no different proportion of age patients malaria positif based the type of malaria parasite(p=1),gender of patient malaria positif based the type of malaria parasite (p=0,429),the type of treatment based the type of malaria parasite (p=1). To reduce the incidence of malaria in the age group 5-14 years old, it is advisable for children to improve protection against mosquite bites. Such as wearing long sleeves when out at night, wear repellent, nets during sleeps and not hang dirty clothes in the room. To suggested to Panyabungan Jae Public Health Center to giving promotion and sosialitation to schools about prevention of malaria. Key Words: Description, Malaria Patients Suspect, Puskesmas Panyabungan Jae